Enantioselective N‐Heterocyclic Carbene Catalysis via the Dienyl Acyl Azolium. (24th March 2018) - Gillard, Rachel M.; Fernando, Jared E. M.; Lupton, David W.
Abstract: Herein we report the enantioselective N‐heterocyclic carbene catalyzed (4+2) annulation of the dienyl acyl azolium with enolates. The reaction exploits readily accessible acyl fluorides and TMS enol ethers to give a range of highly enantio‐ and diastereo‐enriched cyclohexenes (most >97:3 er and >20:1 dr). The reaction was found to require high nucleophilicity NHC catalysts with mechanistic studies supporting a stepwise 1, 6‐addition/β‐lactonization. Abstract : Die 1, 6‐Addition von Enolaten an Dienylacylazolium mit nachfolgender β‐Lactonisierung bietet Zugang zu einer vielseitigen Reihe von polycyclischen β‐Lactonen. Die Reaktion verläuft mit hoher Enantioselektivität, Diastereoselektivität und guten Ausbeuten und stellt das erste Beispiel einer enantioselektiven Katalyse mit Dienylacylazolium, dem höheren Homologen des α, β‐ungesättigten Acylazoliums, dar.